Consumer Perceptions of Commercial Plant-based Milk Alternative Products in Indonesia - Alhusna, Lutfianes Mellinia; Budi, Faleh Setia; Indrasti, Dias (Universitas Djuanda, 2025)
There has been a noticeable shift in consumer preferences from animal-derived milk to plant-based milk alternatives (PBMA). Many scientific studies state that animal milk cannot be replaced by PBMA in term of nutrition. However, not all consumers are aware of this. Therefore, this study aimed to evaluate consumers' perceptions of PBMA. The research was conducted through a regulatory review of PBMA and an online survey using purposive sampling method with 385 PBMA consumers in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) area. Primary data were collected through a respondent survey employing a Likert scale, and analyzed using the Wilcoxon signed-rank test. National Agency of Drug and Food Control (BPOM) categorizes PBMA as a fruit and vegetable-based drink product and therefore prohibited from using the term 'milk' on its label to prevent consumer confusion with animal-derived milk. There was a misperception of respondents towards PBMA. Out of the seven perceptions tested, five were found to be misperceptions, specifically those related to energy, high fat content, source of protein, source of calcium, and causes of allergy. These misperceptions were likely due to respondents’ limited exposure to information about the nutritional content of PBMA. In addition, PBMA were also a relatively new product, and information about it has not been widely disseminated.